(untitled) (Revista Lusófona de Educação, 2018)
In this paper two of the better-known university rankings produced internationally are considered, the Academic Ranking World Universities (ARWU) and the Times Higher Education World Universities Rankings (THE), as well as a national ranking, the Folha University Ranking (RUF), focussed on Brazilian universities. The thesis we put forward is that rankings play a dual role, regulating the market and disseminating organizational models. The paper highlights the existence of differences between the concerns (and implications) of the international rankings (ARWU and THE) and the Brazilian national ranking (RUF), which sets out as main goals, on the one hand, to steer the elites’ demand for tertiary education towards degrees with higher employability and, on the other, to provide indications which may be considered useful for the labour market to recruit better qualified professionals. Keywords: Brazil; universities; rankings; regulation; labour market.